Decentralization, teacher quality, and the education of English learners: Do state education agencies effectively prepare teachers of Els? - Leider, Christine Montecillo; Colombo, Michaela; Nerlino, Erin (Education Policy Analysis Archives, 2021)
English learners are entitled to participate meaningfully and equally in educational programs. The Every Student Succeeds Act (ESSA) includes provisions to ensure success for all students, including English learners. However, the federal government does not prescribe specifically how states should meet these provisions; instead, it is the responsibility of states to develop respective plans of action. This decentralization means that states play a primary role in setting policy for teacher credentialing. In this paper, we address the following question: Do state education agencies effectively prepare teachers of ELs? We reviewed the teacher credentialing requirements to teach classified English learners in bilingual education, English language development, and sheltered English immersion settings, as well as the professional teaching standards for reference to culturally and linguistically diverse learners across the 50 states and the District of Columbia. We found inconsistencies across the US with regard to the education of classified English learners and document wide variation in teacher certification for working with English learners. We highlight implications for policy and teacher preparation.